T cell responses in dengue viral infections. - Malavige, G; Ogg, G (2013)
Dengue viral infections are the commonest mosquito borne viral infection in the world, affecting more than 100 countries and 390 million individuals annually. Currently, there are no effective antiviral drugs or an effective vaccine to prevent infection. A main hurdle in developing a safe and effective vaccine has been our poor understanding of the complex nature of the protective immune response in acute dengue infection and the presence of four dengue virus (DV) serotypes that are highly homologous. The role of DV specific T cells in the pathogenesis of severe clinical disease in not clear. It has been speculated that highly cross reactive T cells for the previous infecting heterologous DV serotype, which produce pro-inflammatory cytokines, contribute to disease pathogenesis. These cross reactive T cells are believed to be suboptimal in clearing the infection with the current DV-serotype. However, other studies have shown that cross-reactive DV-specific T cells are absent or present in very low frequency during acute infection, appearing only during the convalescent period in the majority of patients. Furthermore, significant apoptosis of T cells occurs in severe acute clinical disease. Overall therefore, it is unclear what role T cells play in contributing to disease pathogenesis during acute dengue infection. Existing data have been complicated by cross-reactivity in T cells assays. These findings can now be re-evaluated in the light of novel technologies to identify serotype-specific T cell responses.